Provable security : 11th International Conference, ProvSec 2017, Xi'an, China, October 23-25, 2017, Proceedings /: 11th International Conference, ProvSec 2017, Xi'an, China, October 23-25, 2017, Proceedings. (2017) - Unknown
No abstract available